(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Logical thinking is a necessary cognitive skill that plays an important role in language development and effective communication. This allows an individual to reason, analyze, and communicate, forming a logical and coherent expression of ideas and ideas. In this article, we will study the topic of logical thinking in the language and study its importance in various fields of communication